Digital storytelling: a systematic review - Nur Fatin Nabila Abd Rahman; Rofiza Aboo Bakar (UPT Bahasa Universitas Tanjungpura, 2020)
Digital storytelling (DST) is one of the helpful educational tools in the teaching and learning process. Nonetheless, there is a scarcity of systematic reviews to enlighten how it was applied and what was done in this area. This paper performed a systematic review of five articles on using DST to foster English speaking skills among learners. This research established continuous interest in the background of South-East Asian countries, including learners at the pre-school till tertiary education levels. DST has been used in the humanities and social sciences as either a stand-alone teaching or in conjunction with other teaching techniques. The review classified two directions (ideal and reflective) as well as six outcomes: affective, intellectual, educational, technical, linguistics, and communal. Hence, this study synthesizes and discusses further two issues: affective motivating passion and a creative, imaginative, and resourceful platform. It is hoped this study able to discuss potential explanations for these issues and offer insights for future studies.